Perdas não técnicas na distribuição de eletricidade: estratégias de controle e apoio à tomada de decisão - Savian, Fernando de Souza (2022)
Electricity distribution in Brazil is essential to guarantee the competitiveness of the industrial, commercial and rural sectors and provide social well-being. However, not all the electricity injected into the distribution system reaches the consumer, and the concessionaires do not bill a significant part of the energy consumed. It is also called non-technical loss, generates substantial economic losses, affects the network's quality and reliability, and directly impacts the electricity tariff. In this scenario, concessionaires, regulatory agencies, legislators, and researchers have been developing actions to identify and mitigate non-technical losses and their effects over the last few years in the country. However, fraud schemes are constantly being improved, and delinquency increases as tariffs rise as the population's average income decreases. Furthermore, the socio-economic, geographical, cultural, and technical characteristics of a country with continental dimensions like Brazil make it challenging to select the most efficient methods to combat non-technical losses. Therefore, this thesis proposed an approach that helps Brazilian electricity distribution concessionaires in the decision-making process to identify and mitigate non-technical losses. This thesis proposal was based on a mixed methodological approach, using qualitative techniques, such as a systematic literature review and semi-structured interviews, and quantitative techniques, such as bibliometric analysis and multi-criteria decision analysis. The main results obtained were: (i) an overview of research indicators on non-technical losses in conference proceedings, identifying where the most relevant articles can be found; (ii) a unified definition of non-technical losses; (iii) identification of the main consequences of non-technical losses for countries, concessionaires, and society; (iv) selection of the main barriers for the identification of non-technical losses; (v) selection of the main strategies for identifying non-technical losses; (vi) analysis of the principal regulations and legislation on the subject in the world; (vii) identification of factors that help and hinder the identification and mitigation of non-technical losses in Brazil; (viii) analysis of the current and future scenarios of non-technical losses in the country; (ix) a model that assists in the decision-making process of the concessionaires for the selection of methods for identifying non-technical losses. From an academic perspective, the results expand knowledge on the subject, making unique contributions to the literature. From a practical point of view, the research contributes to the distributors' understanding of the scenario, facilitating the strategic decisionmaking process to combat non-technical losses. The results also guide the formulation of public policies, regulations, and legislation to minimize the effects of non-technical losses in Brazil.